P263 Implementing A New Standard For Medical Specialty Society Guideline Development. (15th August 2013) - Wolfkiel, C; Smith Begolka, W; Fulda, G
Abstract : Background: The Council of Medical Specialty Societies (CMSS) approved "Principles for the Development of Specialty Society Clinical Guidelines" as a set of standards that member societies could draw upon in developing their own development methodologies. Developed by the member societies in late 2012, the Principles are intended to provide a degree of interpretive flexibility not offered by other standard sets but based upon an expected level of transparency that individual interpretations would be explained. Objectives: Principles were labelled as "must", "should" and "may" in an effort to impart suggested implementation flexibility as designed by the Principles development team. This proposed analysis of society feedback is intended to assess the actual concordance with the Principles by societies implementing their methodologies or updating them. Methods: An electronic survey was sent to Societies who identified themselves as creating new or adapting existing methodologies asking agreement on ease of implementation in 10 previously identified contentious standards. The survey will also include opportunity for responders to identify other difficult to implement/interpret principles as well as new principles that should be considered. Results: Data from respondents will be presented. Discussion: Medical Specialty Societies developing clinical practice guidelines are diverse in terms of size, scope and resources. The recent IOM standards were developed by as best practice with little guidance for potential interpretation or resource requirements. The CMSS Principles are intended to be a step towards practical guidelines standards and this research the first feedback step as to measuring that practicality.